Thm 2: Suppose m, n eN are such that n >=m. Then n = m + b if and only if b = n -m. THe problem: If n, m e N with n >= m and n - m = 0, then n = m. I am asked to prove this as a consequence of Thm. 2. Any adivce? THanks.
Follow Math Help Forum on Facebook and Google+
Originally Posted by jzellt Thm 2: Suppose m, n eN are such that n >=m. Then n = m + b if and only if b = n -m. THe problem: If n, m e N with n >= m and n - m = 0, then n = m. I am asked to prove this as a consequence of Thm. 2. Any adivce? THanks. Use theorem 2, but let b=0...
View Tag Cloud